SOCIAL ENVIRONMENT’S INFLUENCE ON CHARLIE’S HARD TIMES IN THE PERKS OF BEING A WALLFLOWER NOVEL - Putri, Yasmin Medina Anggia; Zamruddin, Mardliya Pratiwi; Muhajir, Fatimah (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
Symbolic Interactionism theory by Cooley explains that an individual cannot be separated from society. Individuals or groups of people will interact through communication until they finally enter the social order. Through this interaction, not only actions but also mindsets are changed. This thesis discusses the influence of the social environment on Charlie's hard times in The Perks of Being a Wallflower novel. The purpose of this research is to find out and explain the influence of Charlie's social environment to help him rise from his hard times. These hard times are identified through the conflicts that Charlie faces. This thesis also focuses on Charlie's way of making new friends by interacting with his new friends, Patrick and Sam. In this case, Patrick and Sam are Charlie's social environment. Both of them provide him with various forms of social support: instrumental, tangible, informational, and emotional. The researcher uses symbolic interactionism theory with qualitative research method and a sociological approach in this thesis. Based on the analysis, Charlie, the main character, managed to get through his hard times because of his friendship with Patrick and Sam. It can be seen from the way they interact until Charlie receives all types of social support from Patrick and Sam. Charlie was given gifts, advice, entertainment, attention, love, and care. In this thesis, the researcher also found that the presence of a social environment for Charlie, who is going through hard times, has a big impact on his ability to finally be confident, feel loved by his family and friends, and be able to get along with other people around him besides Patrick and Sam. Charlie has also stated that he will begin to become preoccupied with interacting with other people in real life. He said he would not write letters so often anymore and would participate with other people.